2023
DOI: 10.1177/03331024221131343
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical features of hemicrania continua in clinic-based studies: A systematic review and meta-analysis

Abstract: Objective To estimate the relative frequencies of hemicrania continua and its clinical features in adult patients who were evaluated for headache in a clinic-based setting. Methods PubMed and Embase were searched for observational, clinic-based studies published between 1 January 2004 and 1 February 2022, that reported on the relative frequencies of hemicrania continua and its clinical features. Two independent investigators (HMA and SA-K) screened titles, abstracts, and full text-articles. A random-effects me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Both respond absolutely to indomethacin 1 . A recent meta‐analysis suggests hemicrania continua is more common in tertiary care settings, compared with our estimates for paroxysmal hemicrania 36 …”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Both respond absolutely to indomethacin 1 . A recent meta‐analysis suggests hemicrania continua is more common in tertiary care settings, compared with our estimates for paroxysmal hemicrania 36 …”
Section: Discussionmentioning
confidence: 49%
“…1 A recent meta-analysis suggests hemicrania continua is more common in tertiary care settings, compared with our estimates for paroxysmal hemicrania. 36 Migraine is also an important differential diagnosis to consider when evaluating patients with suspected paroxysmal hemicrania.…”
Section: Differential Diagnosesmentioning
confidence: 99%
“…Apart from the constant unilateral headache and autonomic symptoms, features of migraine are commonly seen in HC and PH patients. Symptoms including nausea, vomiting, photophobia, and phonophobia are reported (2,3,8,11). In this cohort, most of the patients reported some migrainous features as well.…”
Section: Discussionmentioning
confidence: 99%
“…According to the International Classification of Headache Disorders, 3rd edition (ICHD-3), HC is defined as unilateral headache that persists for more than three months, with at least one of the ipsilateral autonomic symptoms including conjunctival injection, lacrimation, nasal congestion, rhinorrhea, eyelid oedema, facial sweating, miosis or ptosis and a therapeutic response to indomethacin (1). A recent review suggested the three most common symptoms associated with HC were lacrimation, conjunctival injection and restlessness or agitation (11). PH is defined as severe unilateral headache lasting for 2-30 minutes with ipsilateral autonomic features.…”
Section: Introductionmentioning
confidence: 99%
“…As with PH, there are no population-based prevalence data as the diagnosis is reliant upon a therapeutic response to indometacin. From a meta-analysis of adults attending headache clinics, an estimate of relative frequencies was found to be 1.8% (73).…”
Section: Hemicrania Continuamentioning
confidence: 99%